1989
DOI: 10.1161/01.cir.79.3.573
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of patients undergoing percutaneous mitral balloon valvotomy. Analysis of factors determining restenosis.

Abstract: This study reports the clinical follow-up (13±1 months) of 100 consecutive patients who underwent percutaneous mitral balloon valvotomy (PMV). Echocardiographic (n=32) and cardiac catheterization (n=37) data from this group are also included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
4
10

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(88 citation statements)
references
References 21 publications
9
65
4
10
Order By: Relevance
“…Percutaneous mitral balloon valvuloplasty (PBMV) is an effective therapy in patients with symptomatic mitral stenosis (MS) [1][2][3]. In addition, PBMV is the best choice for isolated MS with favorable morphology [4].…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous mitral balloon valvuloplasty (PBMV) is an effective therapy in patients with symptomatic mitral stenosis (MS) [1][2][3]. In addition, PBMV is the best choice for isolated MS with favorable morphology [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, using the same definition, reported success rates ranging from 70 to 90%. 3,17 In all patients, PMV was performed with the Inoue balloon technique. The main advantages of this technique (versus the double-balloon technique) are the absence of a guidewire in the left ventricle, the self-positioning of the balloon, and the ability to perform stepwise inflations under echo guidance to monitor commissural opening.…”
Section: Discussionmentioning
confidence: 99%
“…• Sucesso: aumento da área valvar ≥ 25% da área inicial e área valvar mitral final ≥ 1,5 cm², na ausência de insuficiência mitral grave [6][7][8][9][10][11] .…”
Section: Definiçõesunclassified
“…• Reestenose ecocardiográfica: área valvar mitral no seguimento tardio, avaliada pela planimetria e/ou pelo tempo de meia pressão (PHT), < 1,5 cm², com perda ≥ 50% do ganho inicial [7][8][9] .…”
Section: Definiçõesunclassified